2015
DOI: 10.1088/0067-0049/221/1/10
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde Masers: Exclusive Tracers of High-Mass Star Formation

Abstract: The detection of four formaldehyde (H 2 CO) maser regions toward young high-mass stellar objects in the last decade, in addition to the three previously known regions, calls for an investigation of whether H 2 CO masers are an exclusive tracer of young high-mass stellar objects. We report the first survey specifically focused on the search for 6 cm H 2 CO masers toward non high-mass star-forming regions (non HMSFRs). The observations were conducted with the 305 m Arecibo Telescope toward 25 low-mass star-formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 69 publications
(76 reference statements)
2
14
0
Order By: Relevance
“…The 6 cm line of formaldehyde (H 2 CO) is a rare maser transition that has been reported toward nine HMSFRs in our Galaxy: NGC 7538 IRS 1 (Downes & Wilson 1974;Hoffman et al 2003), Sgr B2 (Whiteoak & Gardner 1983;Mehringer et al 1994;Hoffman et al 2007), G29.96−0.02 (Pratap et al 1994;Hoffman et al 2003), IRAS 18566+0408 (G37.55+0.20; Araya et al 2004b), G23.71−0.20 (Araya et al 2006), G23.01−0.41 (Araya et al 2008), G25.83−0.18 (Araya et al 2008), G32.74−0.07 (Araya et al 2015), and G0.38+0.04 (Ginsburg et al 2015), and three extragalactic regions (Baan et al 1986;Araya et al 2004a; see however Mangum et al 2008). …”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The 6 cm line of formaldehyde (H 2 CO) is a rare maser transition that has been reported toward nine HMSFRs in our Galaxy: NGC 7538 IRS 1 (Downes & Wilson 1974;Hoffman et al 2003), Sgr B2 (Whiteoak & Gardner 1983;Mehringer et al 1994;Hoffman et al 2007), G29.96−0.02 (Pratap et al 1994;Hoffman et al 2003), IRAS 18566+0408 (G37.55+0.20; Araya et al 2004b), G23.71−0.20 (Araya et al 2006), G23.01−0.41 (Araya et al 2008), G25.83−0.18 (Araya et al 2008), G32.74−0.07 (Araya et al 2015), and G0.38+0.04 (Ginsburg et al 2015), and three extragalactic regions (Baan et al 1986;Araya et al 2004a; see however Mangum et al 2008). …”
Section: Introductionsupporting
confidence: 68%
“…In addition, masers and megamasers have been found in extragalactic environments (e.g., Baan 1985;Haschick et al 1994;Lo 2005;Sjouwerman et al 2010). There are several types of masers which have been detected exclusively in high-mass star forming regions (HMSFR) including 6.7 and 12.2 GHz methanol and 6 cm (4.83 GHz) formaldehyde masers (e.g., Walsh et al 1998;Breen et al 2013;Araya et al 2007a;Araya et al 2015). These masers are not only signposts of high-mass star formation but also help trace small-scale dynamics, morphology, and the locations of outflows and accretion disks (e.g., Bartkiewicz et al 2009;Sanna et al 2010;Goddi et al 2011;Torrelles et al 2011;Moscadelli et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The 4765 MHz line corresponds to the transition 2 Π 1/2 J = 1/2 F = 1 − 0 (E u = 181.94 K) 3 , which is analogous to the 1720 MHz OH ground state line but in the 2 Π 1/2 ladder instead of the 2 Π 3/2 (e.g., Pihlström et al 2008, see also Figure 5.2 in Gray 2012). The emission was first detected in the May 2008 observations (Araya et al 2015), and then confirmed in October 2008. Figure Table 1.…”
Section: Resultsmentioning
confidence: 87%
“…However, using the 305 m Arecibo Telescope, we have detected a narrow line corresponding to the 4765 MHz transition of OH. The detection of this line was a by-product of a survey for H 2 CO masers reported in Araya et al (2015). In this work we focus on the 4765 MHz OH detection, and present complementary observations also conducted with the Arecibo Telescope.…”
Section: Introductionmentioning
confidence: 95%
“…Example spectra from two epochs, first detection (upper panel; see observation details inAraya et al 2015) and 2017 (lower panel) non-detection. The upper panel shows a high spectral resolution spectrum (blue-dashed) and the smoothed spectrum (black-solid).…”
mentioning
confidence: 99%